Computer security literacy staying safe in a digital world - Jacobson, Douglas (CRC Press / Taylor & Francis Group, 2013)
Preface Approach Traditional computer security books educate readers about a multitude of topics, ranging from secure programming practices, protocols, and algorithm designs to cryptography and ethics. These books typically focus on the implementation or theory of security controls and mechanisms at the application, operating system, network, and physical layers. Breaking this traditional model, "Computer Security Literacy: Staying Safe in a Digital World" instead seeks to educate the reader at the user layer and focuses on practical topics that one is likely to encounter on a regular basis. It has long been recognized that the user is in fact the weakest link in the security chain. So why not effect change by providing practical and relevant education for the normal user of information technology? As it turns out, we, the user, often have the greatest impact in the security of our computer and information as a result of the actions that we do or do not perform. This text provides practical security education to give the reader context to make sound security decisions. The outcomes of this book are as follows. The reader will be able to: - Define computer security terms and mechanisms - Describe fundamental security concepts - State computer security best practices - Describe the strengths, weaknesses, and limitations of security mechanisms and concepts - Give examples of common security threats, threat sources, and threat motivations - Explain their role in protecting their own computing environment and personal and confidential information - Discuss current event topics and read security articles in the popular press - Assess computing actions in the context of security.